2023
DOI: 10.1080/15548627.2023.2167689
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy in microglia and macrophages exacerbates innate immune responses and worsens brain injury outcomes

Abstract: Excessive and prolonged neuroinflammation following traumatic brain injury (TBI) contributes to long-term tissue damage and poor functional outcomes. However, the mechanisms contributing to exacerbated inflammatory responses after brain injury remain poorly understood. Our previous work showed that macroautophagy/autophagy flux is inhibited in neurons following TBI in mice and contributes to neuronal cell death. In the present study, we demonstrate that autophagy is also inhibited in activated microglia and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In recent years, researchers have begun to focus on the effect of autophagy on the polarization of microglia. A study further confirmed that autophagy is inhibited in activated microglia and that this change promotes brain injury-induced neuroinflammatory responses (Hegdekar et al, 2023). Inhibition of autophagy attenuates microglial phagocytosis, resulting in the accumulation of damaged neurons and an inflammatory response (Beccari et al, 2023).…”
Section: Autophagy Regulates Microglial Activationmentioning
confidence: 77%
“…In recent years, researchers have begun to focus on the effect of autophagy on the polarization of microglia. A study further confirmed that autophagy is inhibited in activated microglia and that this change promotes brain injury-induced neuroinflammatory responses (Hegdekar et al, 2023). Inhibition of autophagy attenuates microglial phagocytosis, resulting in the accumulation of damaged neurons and an inflammatory response (Beccari et al, 2023).…”
Section: Autophagy Regulates Microglial Activationmentioning
confidence: 77%
“…Raised SQSTM1 in acute TBI was associated with less axonal injury, as measured on DTI, supporting a role for post-injury autophagy in mitigating axonal injury. Indeed, experimental TBI studies have shown that impaired autophagy by microglial and macrophages exacerbates worse post-injury neuroinflammation, through reduced clearance of DAMPs and proinflammatory signals, such as the NLRP3 inflammasome, and worsens outcomes 9 .…”
Section: Discussionmentioning
confidence: 99%
“…74 Autophagy in microglia may project beyond such a backup role, becoming an important element of their immune functions. 75 So far, autophagy in the CNS has been studied in neurons, mainly in their axons, to show its role in neuronal transmission. 11,18,19,76 As we stated above, mechanisms of autophagy in microglia are less known-in fact, it is not clear whether microglial autophagy occurs with the involvement of the main proteins of canonical autophagy; 77 therefore, it is difficult to anticipate the consequences of blocking MA in microglia in the context of overall cellular autophagic response.…”
Section: Mig R Aine-rel Ated Effec Ts May Impair M Acroauto Ph Agy In...mentioning
confidence: 99%
“…Phagocytosis, a primary mechanism to eliminate pathogens, has much in common with autophagy and when phagocytosis fails, autophagy can take its role acting as a backup system to fight invaders 74 . Autophagy in microglia may project beyond such a backup role, becoming an important element of their immune functions 75 . So far, autophagy in the CNS has been studied in neurons, mainly in their axons, to show its role in neuronal transmission 11,18,19,76 .…”
Section: Migraine‐related Effects May Impair Macroautophagy In and Fa...mentioning
confidence: 99%